Exploring Opportunities for Platinum Nanoparticles Encapsulated in Porous Liquids as Hydrogenation Catalysts. Issue 31 (18th March 2020) - Hemming, Ellen B.; Masters, Anthony F.; Maschmeyer, Thomas
Abstract: The unusual combination of characteristics observed for porous liquids, which are typically associated with either porous solids or liquids, has led to considerable interest in this new class of materials. However, these porous liquids have so far only been investigated for their ability to separate and store gases. Herein, the catalytic capability of Pt nanoparticles encapsulated within a Type I porous liquid (Pt@HS‐SiO2 PL) is explored for the hydrogenation of several alkenes and nitroarenes under mild conditions ( T= 40 °C, P H2 =1 atm). The different intermediates in the porous liquid synthesis (i.e., the initial Pt@HS‐SiO2, the organosilane‐functionalized intermediate, and the final porous liquid) are employed as catalysts in order to understand the effect of each component of the porous liquid on the catalysis. For the hydrogenation of 1‐decene, the Pt@HS‐SiO2 PL catalyst in ethanol has the fastest reaction rate if normalized with respect to the concentration of Pt. The reaction rate slows if the reaction is completed in a "neat" porous liquid system, probably because of the high viscosity of the system. These systems may find application in cascade reactions, in particular, for those with mutually incompatible catalysts. Abstract : Porous liquids for catalysts : Platinum nanoparticles encapsulated within a Type I porous liquid are successfully employed for the first time as hydrogenation catalysts. In addition, this work explores the effect of each component of the corona‐canopy on the catalytic activity.